Exciton polariton interactions in Van der Waals superlattices at room temperature - Zhao, Jiaxin (2023)
Monolayer transition-metal dichalcogenide (TMD) materials have attracted a great attention because of their unique properties and promising applications in integrated optoelectronic devices. Being layered materials, they can be stacked vertically to fabricate artificial van der Waals lattices, which offer unique opportunities to tailor the electronic and optical properties. The integration of TMD heterostructures in planar microcavities working in strong coupling regime is particularly important to control the light-matter interactions and form robust polaritons, highly sought for room temperature applications. Here, we demonstrate the systematic control of the coupling-strength by embedding multiple WS2 monolayers in a planar microcavity. The vacuum Rabi splitting is enhanced from 36 meV for one monolayer up to 72 meV for the four-monolayer microcavity. In addition, carrying out time-resolved pump-probe experiments at room temperature we demonstrate the nature of polariton interactions which are dominated by phase space filling effects. Furthermore, we also observe the presence of long-living dark excitations in the multiple monolayer superlattices. Our results pave the way for the realization of polaritonic devices based on planar microcavities embedding multiple monolayers and could potentially lead the way for future devices towards the exploitation of interaction-driven phenomena at room temperature.